SOME COMMENTS ON THE USE OF LATIN CHEMICAL TERMS IN MEDICINE (Journal of Universal Science Research, 2024)
This article discusses the naming, dictionary form, and usage of chemical terms used in medicine in Latin and English. In addition to naming chemical terms in medicine in terms of form, they are also used in other sciences with the same name, their properties are complete. information is provided.